2002
DOI: 10.1051/0004-6361:20011738
|View full text |Cite
|
Sign up to set email alerts
|

The CORALS survey

Abstract: Abstract. We present a list of z abs ∼ zem (∆v < 3000 km s −1 ) DLAs discovered during the CORALS survey for absorbers in a radio-selected QSO sample. On the assumption that z abs ∼ zem DLAs are neither ejecta from the QSO, nor part of the host galaxy itself, we use the number density statistics of these DLAs to investigate galaxy clustering near the QSO redshift. We find that n(z) of z abs ∼ zem DLAs in our radio-selected QSO sample is ∼4 times larger than the number density of intervening DLAs, implying an e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
160
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(180 citation statements)
references
References 46 publications
18
160
1
Order By: Relevance
“…In addition, it seems that the RLQs generally reside in richer environments than RQQs (Ellison et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it seems that the RLQs generally reside in richer environments than RQQs (Ellison et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It has provided the basis for a study of damped Lyman-α absorption systems along the lines of sight to the quasars (Ellison et al 2001(Ellison et al , 2002. In this paper we also Send offprint requests to: I. M. Hook, e-mail: imh@astro.ox.ac.uk Table A.1 is also available in electronic form at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsweb.u-strasbg.fr/cgi-bin/qcat?J/A+A/399/469…”
Section: Introductionmentioning
confidence: 99%
“…The first results, reported by Ellison et al (2001), showed that Ω DLA had not been significantly underestimated. To that conclusion we now add the findings that:…”
Section: Discussionmentioning
confidence: 98%
“…They found values which were only marginally higher than the corresponding quantities previously determined from optically selected QSO samples. In particular, within the limitations imposed by the small size of their sample, Ellison et al (2001) concluded that selection effects due to intervening dust may at most account for an underestimate by a factor of ∼2 in Ω DLA .…”
Section: The Corals Samplementioning
confidence: 99%